The Phenomenon of Culture Shock in New Students in the City of Surabaya - Sita Atika Putri M; Ciara Fidela Katalaniya; Aklis Syafa Pratiwi; Fahrudi Ahwan Ikhsan; Saiful Amin (International Journal of Geography, Social, and Multicultural Education, 2024)
Generally, to get better higher education, individuals are willing to migrate to cities with adequate educational facilities. Surabaya is one of the big cities in Indonesia with many universities that provide a variety of educational programs, making Surabaya a choice for migrants. When you first live in the city of Surabaya as an overseas city, individuals will of course experience shock with the new culture and environment, so it takes time to get used to the situation in the city of Surabaya. This situation is called culture shock. Culture Shooc is an event that generally occurs when an individual is in a place that is different from their living environment. This article was created to find out how the phenomenon of culture shock is felt by overseas students and the causes and impacts of culture shock that is felt. The results of this research show that the culture shock phenomenon often occurs in the early days of life in the city of Surabaya. Culture shock occurs due to environmental and cultural differences between the place of origin and the city of Surabaya. Over time, overseas students will get used to and be able to adapt to the conditions in the city of Surabaya. This research uses primary data collected through interviews with three informants, namely Kurnia (20 years), Sabrina (17 years), and Lisa (19 years), their current status is overseas students studying in the city of Surabaya.